PENERAPAN METODE NIJ UNTUK ANALISIS SERANGAN DOS PADA PERANGKAT IOT - Singgih Mitro S; Dadan Sukma (Politeknik Harapan Bersama Tegal, 2023)
One of the problems of IoT is because many devices are connected to IoT in the industrial era 4.0, which ultimately distracts hackers from solving security mechanisms. One of the security factors of concern in this IoT device is a Denial of Service (DoS) attack on the Internet of Things (IoT) device network which results in a system being flooded with data continuously in a short time resulting in very dense network traffic. resulting in IoT device down. This study aims to apply the National Institute of Justice (NIJ) method in analyzing Denial of Service (DOS) attacks on Internet of Things (IoT) devices. The NIJ method includes stages such as preparation, incident handling, collection identification, collection, examination, analysis, reporting. The results of the study show that the NIJ method can be used to analyze DoS attacks on IoT devices and assist in taking action to prevent further attacks.